2019
DOI: 10.1136/bmjopen-2018-022098
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a prospective, longitudinal, cohort study of recovery pathways, acute biomarkers and cost for children with persistent postconcussion symptoms: the Take CARe Biomarkers study

Abstract: IntroductionThe majority of children who sustain a concussion will recover quickly, but a significant minority will experience ongoing postconcussive symptoms, known as postconcussion syndrome (PCS). These symptoms include emotional, behavioural, cognitive and physical symptoms and can lead to considerable disability. The neurobiological underpinnings of PCS are poorly understood, limiting potential clinical interventions. As such, patients and families frequently re-present to clinical services, who are often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…16 The protocol for the Take CARe study can be found in the article by Takagi and coworkers. 17 In brief, the study recruited and assessed children presenting with concussion to the ED and then followed up with the children 1-4 days, 2 weeks, 1 month, and 3 months postinjury. Multiple domains of functioning were assessed at each time point (concussive symptoms, neurocognition, behavior, quality of life, fatigue).…”
Section: Designmentioning
confidence: 99%
“…16 The protocol for the Take CARe study can be found in the article by Takagi and coworkers. 17 In brief, the study recruited and assessed children presenting with concussion to the ED and then followed up with the children 1-4 days, 2 weeks, 1 month, and 3 months postinjury. Multiple domains of functioning were assessed at each time point (concussive symptoms, neurocognition, behavior, quality of life, fatigue).…”
Section: Designmentioning
confidence: 99%
“…Data were collected as part of the ‘Take CARe’ (Concussion Assessment and Recovery Research) study, a single site, prospective, longitudinal study of children and adolescents (referred to as children) presenting to the emergency department (ED) of a tertiary paediatric hospital with a diagnosis of concussion. See Bressan et al 21 and Takagi et al 22 for full details.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a larger single site, prospective, longitudinal study (Take CARe Biomarkers – Concussion Assessment and Recovery research) conducted at a state-wide tertiary pediatric hospital in Melbourne, Australia (see Takagi et al, (2019) for full study details). In brief, the study recruited and assessed children presenting with concussion to the emergency department (ED) and then followed up with the children 1–4 days, two weeks, one month, and three months post-injury.…”
Section: Methodsmentioning
confidence: 99%